Synthesis Of Microwave-Assisted Coconut Shell Based Activated Carbon For Removal Of Methylene Blue Dye From Aqueous Solution - Nordin, Nazatul Shima (Universiti Sains Malaysia, 2018)
The hazardous dye effluent from the textile, paper, cosmetic and food processing plant have become a major concern because of the toxicity to the environment. This study aims to synthesis activated carbon (AC) derived from coconut shell (CS) in order to remove methylene blue (MB) dye from aqueous solution. The coconut shell based activated carbon (CSAC) was prepared via physical activation process by using microwave irradiation under the flow of carbon dioxide (CO2) gasification. The effect of contact time (0-24 hours), initial concentration (25mg/L-300mg/L) and temperature (30˚C, 45˚C and 60˚C) on the adsorption performance of CSAC were evaluated. Optimum condition for the CSAC preparation was obtained at power and time of 440W and 6 minutes, respectively by using response surface methodology (RSM). The optimized CSAC has high BET surface area, mesopore surface area, total pore volume and fixed carbon of 658.44m2/g, 502.31m2/g, 0.4898cm3/g and 82.13%, respectively. The pore for CSAC was the mesoporous type with pore diameter of 5.72nm. Langmuir isotherm and pseudo-second-order was found as the best fitted model for MB adsorption equilibrium and kinetic onto CSAC. The monolayer adsorption capacity of MB onto CSAC was 217.3 mg/g. The adsorption system was endothermic in nature and it was governed by physisorption. The mechanism studies revealed that the adsorption process of MB onto CSAC were controlled by film diffusion mechanism.